KINETIC INVESTIGATION OF CARBON DIOXIDE, ACETIC ACID, ACRYLIC ACID FORMATION ON DILUTED AND LEACHED MoVTeNb CATALYST - Restu Kartiko Widi (Indonesian Journal of Chemistry, 2012)
Reaction kinetics for the oxidation of propane over diluted-leached MoVTeNb is described. This paper is focused on the study of determination of the orders of carbon dioxide, acetic acid and acrylic acid formation. Deep oxidation of propane to carbon dioxide is first order with respect to hydrocarbon, and partial order (0.31) with respect to oxygen. The selective oxidation of propane to acrylic acid is partial order (0.49) with respect to hydrocarbon and partial order (0.09) with respect to oxygen.